Impact of Instagram Posts, Instagram Stories, and Instagram Reels on Brand Awareness of Muslim Clothing Brand Zombasic - Junaidi Safitri (Journal of Islamic Economics Lariba, 2022)
This study analyzes how the use of Instagram posts, Instagram stories, and Instagram reels impact brand awareness of the Muslim clothing brand Zombasic. This study uses quantitative research methods with multiple linear regression data analysis techniques. This research was conducted using data obtained from online questionnaires, with a total population of 236,000 followers and a sample of 100 respondents with the criteria of active Instagram users following the Zomabasic Instagram account. The results partially show that using the Instagram post feature does not have an effective and significant impact on brand awareness, with a variable coefficient value of 0.031. The use of the Instagram Stories feature has an effective and significant impact on brand awareness with a variable coefficient value of 0.710, and the use of the Instagram reels feature has an effective and significant impact on brand awareness with a variable coefficient value of 0.223. The results show a coefficient of determination (R²) value of 69%, which means that the use of the Instagram Post, Stories, and Reels features have an effective level of 69%.